Density functional theory study of hydrogen storage by spillover on graphene and boron nitride sheet: doping effect and the kinetic issues - Wu, Hongyu (2012)
The lack of efficient hydrogen storage materials has hindered the potential use of hydrogen as fuel for transportation, personal electronics and other portable power applications. Hydrogen spillover has been experimentally demonstrated to be an effective approach for hydrogen storage applications. To have a fundamental understanding of the hydrogen spillover mechanism, theoretical investigations on the doping effect and the kinetic issues of the hydrogen storage by spillover on graphene and boron nitride sheet have been carried out in this thesis.